2014
DOI: 10.1292/jvms.14-0108
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Promotes Invasion of Feline Mammary Carcinoma Cells

Abstract: The serum amyloid A (SAA) concentration is higher in mammary tumors with metastases in both humans and animals. In the present study, the direct effects of recombinant feline SAA (rfSAA) protein on invasiveness of feline mammary carcinoma cells were evaluated. As an indicator of invasiveness, matrix metalloproteinase-9 (MMP-9) expression was investigated in 4 feline mammary carcinoma cell lines of different origins. In 3 of 4 cell lines, MMP-9 expression was significantly increased by rfSAA stimulation. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Increases in circulating CRP, SAA and Hp have been detected in female dogs with mammary cancer with metastasis in regional lymph nodes and/or distant organs (clinical stages IV and V) when compared with diseased females without metastasis and also with controls in the study of Tecles et al 22 however, no significant differences in CRP or Hp were detected between diseased dogs with and without lymph node metastasis in the study of Planellas et al 23 In the feline species, an in vitro study showed that SAA promotes invasion of mammary carcinoma cells. 60 In addition, higher concentrations of enzymatic antioxidants, including GPox, were described in neoplastic tissues of bitches with mammary tumours in clinical stages III and IV when compared with animals with mammary tumours of clinical stages I and II. 57 In the present study, serum Hp at diagnosis was higher in cases of neoplasms with vascular invasion, with metastasis in regional lymph nodes and with metastasis in distant organs, suggesting that it might be clinically useful in assessment of metastatization of feline mammary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in circulating CRP, SAA and Hp have been detected in female dogs with mammary cancer with metastasis in regional lymph nodes and/or distant organs (clinical stages IV and V) when compared with diseased females without metastasis and also with controls in the study of Tecles et al 22 however, no significant differences in CRP or Hp were detected between diseased dogs with and without lymph node metastasis in the study of Planellas et al 23 In the feline species, an in vitro study showed that SAA promotes invasion of mammary carcinoma cells. 60 In addition, higher concentrations of enzymatic antioxidants, including GPox, were described in neoplastic tissues of bitches with mammary tumours in clinical stages III and IV when compared with animals with mammary tumours of clinical stages I and II. 57 In the present study, serum Hp at diagnosis was higher in cases of neoplasms with vascular invasion, with metastasis in regional lymph nodes and with metastasis in distant organs, suggesting that it might be clinically useful in assessment of metastatization of feline mammary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to be increased in immune-mediated diseases, in tumors with inflammation, in infections, specifically those caused by Hemoplasma spp. [9], as well as in urinary tract disorder, post-surgery [4], pancreatitis [10], injury, infection-related disease, feline lower urinary tract disease, tumor, hyperthyroidism, diabetes mellitus [5,11,12], renal disease [5,7,13,14], mammary tumors [15], lymphoma, mesothelioma [16], feline infectious peritonitis [5,7,17,18], and sepsis [19], and is reported to be useful as a diagnostic aid. These reports include endocrine diseases not generally associated with inflammation, such as hyperthyroidism or diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the results of this meta- analysis should be more stable. Previous studies have found that SAA can distinguish lung cancer patients from healthy controls as well as predict prognosis of lung cancer [8, 12, 15, 17]. SAA is secreted during the acute phase of inflammation, including invertebrates and vertebrates, suggests that SAA has an essential role in all animals including humans [15].…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A (SAA), a kind of cytokine-induced, acute inflammatory response proteins, has been known to be likely involved in cancers [7]. Research shows that liver is mainly workplace for producing SAA protein which can stimulates the production of various cytokines, and SAA plays an important role in acute immune response [8]. SAA protein in blood of patients with cancer often rises at its early stage, which have been identified both by immunochemistry and by proteomics methods in different cancers, such as lung, ovarian, renal, uterine, nasopharyngeal cancer and in melanoma [7].…”
Section: Introductionmentioning
confidence: 99%